Perhitungan Overall Equipment Effectiveness (OEE) untuk Mengetahui Efektivitas Mesin Produksi di PT. Z - Marcello Aprialdo; Fahriza Nurul Azizah (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
PT. Z is a company that produces all packaging needs. The problems that exist in the production process are frequent occurrence of breakdowns on machines which result in decreased productivity. This study aims to calculate the Overall Equipment Effectiveness (OEE) value, analyze the six big losses factors, and analyze the root causes of problems from the Imprabox Matt Floor production process. From the results of the calculations that have been done, it is found that the OEE value of the Marking Process is 85.2%, Material Cutting is 68.2%, Material Printing is 75.8%, Printing is 47.9%, Welding Process is 36.6%, Assembly is 74.9% , Process Screw 81.3%. Only the marking process meets World Class OEE with an OEE value of 85.2%, and the smallest OEE value of all production processes is found in the welding process with an OEE value of 36.6%. The results of the Six Big Losses analysis and the root causes of the problem found that the lack of understanding of employees in operating machines is one of the main causes of the low OEE score. From these problems, proposed improvements in an effort to increase OEE are by conducting operator training, scheduling preventive maintenance, making machine checksheets, standardizing the welding process, and checking the machine periodically. Keywords: Cause and Effect Diagrams, OEE, Productivity, Six Big Losses